2021
DOI: 10.1039/d1ra05096f
|View full text |Cite
|
Sign up to set email alerts
|

Convergent synthesis of 2-thioether-substituted (N)-methanocarba-adenosines as purine receptor agonists

Abstract: Enabling efficient synthesis of rigid methanocarba nucleotides and nucleosides as clinically promising purinergic receptor ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…1 H-NMR (600 MHz, CD3OD) δ (ppm) = 8.47 (s, 1H, 2-CHimidazopyridine), 7.39-7.35 (m, 2H, 2, 6-CHbenzyl), 7.32 (dd, J = 8.5, 6.8 Hz, 2H, 3, 5-CHbenzyl), 7.28-7.23 (m, 1H, 4-CHbenzyl), 6.36 (s, 1H, 6-CHimidazopyridine), 5.48 (s, 0.2H, CH2Cl2, solvent: dichloromethane), 4.83 (s, 1H, 4-CH), 4.76 (dd, J = 6.7, 1.7 Hz, 1H, 2-CH), 4.57 (s, 2H, CH2 benzyl), 4.27 (dd, J = 11.6, 0.9 Hz, 1H, OCHH), 3.84 (dt, J = 6.7, 1.2 Hz, 1H, 3-CH), 3.32 (d, J = 11.5 Hz, 1H, OCHH), 1.62 (ddd, J = 8.8, 3.9, 1.5 Hz, 1H, 5-CH), 1.55 (dd, J = 5.2, 3.9 Hz, 1H, 6-CHH), 0.74 (ddd, J = 8.7, 5.2, 1.8 Hz, 1H, 6-CHH). 13 (14) Compound 13 (0.10 g, 0.15 mmol) was dissolved in DMF (5.5 mL). NaSCH3 (0.21 g, 3.04 mmol, 20 eq.)…”
Section: (1r2r3s4r5s)-4-[7-(benzylamino)-5-chloro-3h-imidazo[45-b]pyr...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H-NMR (600 MHz, CD3OD) δ (ppm) = 8.47 (s, 1H, 2-CHimidazopyridine), 7.39-7.35 (m, 2H, 2, 6-CHbenzyl), 7.32 (dd, J = 8.5, 6.8 Hz, 2H, 3, 5-CHbenzyl), 7.28-7.23 (m, 1H, 4-CHbenzyl), 6.36 (s, 1H, 6-CHimidazopyridine), 5.48 (s, 0.2H, CH2Cl2, solvent: dichloromethane), 4.83 (s, 1H, 4-CH), 4.76 (dd, J = 6.7, 1.7 Hz, 1H, 2-CH), 4.57 (s, 2H, CH2 benzyl), 4.27 (dd, J = 11.6, 0.9 Hz, 1H, OCHH), 3.84 (dt, J = 6.7, 1.2 Hz, 1H, 3-CH), 3.32 (d, J = 11.5 Hz, 1H, OCHH), 1.62 (ddd, J = 8.8, 3.9, 1.5 Hz, 1H, 5-CH), 1.55 (dd, J = 5.2, 3.9 Hz, 1H, 6-CHH), 0.74 (ddd, J = 8.7, 5.2, 1.8 Hz, 1H, 6-CHH). 13 (14) Compound 13 (0.10 g, 0.15 mmol) was dissolved in DMF (5.5 mL). NaSCH3 (0.21 g, 3.04 mmol, 20 eq.)…”
Section: (1r2r3s4r5s)-4-[7-(benzylamino)-5-chloro-3h-imidazo[45-b]pyr...mentioning
confidence: 99%
“…The introduction of the bicyclo[3.1.0]hexane scaffold, also known as (N)-methanocarba (N for North), in place of the furanose ring of nucleoside agonists is known to increase the A3 receptor (A3AR) potency and selectivity in comparison to other adenosine receptor subtypes [11,12]. In 2005 Jacobson et al reported compounds 1a and 1b as highly potent A3 receptor agonists [13] and, most recently the synthesis of S-thioether (N)-methanocarba adenosine derivatives such as compound 2 (Figure 1) [14]. We were interested in exploring these scaffolds further through various substitutions at 6-position of the purine ring (purine numbering), the introduction of the 1-deazapurine scaffold, and variations of the 5'-position (ribose numbering) at the methanocarba moiety (Figure 1, general structure I).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the bicyclo[3.1.0]hexane scaffold, also known as (N)-methanocarba (N for North), in place of the furanose ring of nucleoside agonists is known to increase the A 3 receptor (A 3 AR) potency and selectivity in comparison to other adenosine receptor subtypes [ 11 , 12 ]. In 2005 Jacobson et al reported compounds 1a and 1b as highly potent A 3 receptor agonists [ 13 ] and most recently, the synthesis of S-thioether (N)-methanocarba adenosine derivatives such as compound 2 ( Figure 1 ) [ 14 ]. We were interested in exploring these scaffolds further through various substitutions at 6-position of the purine ring (purine numbering), the introduction of the 1-deazapurine scaffold, and variations of the 5′-position (ribose numbering) at the methanocarba moiety ( Figure 1 , general structure I ).…”
Section: Introductionmentioning
confidence: 99%